2021
DOI: 10.1016/j.plantsci.2021.110845
|View full text |Cite
|
Sign up to set email alerts
|

The endosperm cavity of wheat grains contains a highly hydrated gel of arabinoxylan

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…It is worth noting that the EC described here is different from that of the EC in wheat. The latter is designated as a gap between the endosperm and the maternal tissue ( Chateigner-Boutin et al, 2021 ) from which nutrients are taken up by the filial tissues. By contrast, the EC in maize grain represents a hollow space within the basal region of the endosperm ( Figure 1A ).…”
Section: Resultsmentioning
confidence: 99%
“…It is worth noting that the EC described here is different from that of the EC in wheat. The latter is designated as a gap between the endosperm and the maternal tissue ( Chateigner-Boutin et al, 2021 ) from which nutrients are taken up by the filial tissues. By contrast, the EC in maize grain represents a hollow space within the basal region of the endosperm ( Figure 1A ).…”
Section: Resultsmentioning
confidence: 99%
“…The only detail of the inside of cells revealed by X-rays is the presence of starch grains in the endosperm that are particularly highlighted due to their high density. The endosperm cavity, which contains water, proteins, and carbohydrates, is visible in the ventral crease region although its shape appears different than in microscopy images of grain sections where it is altered and emptied by preparation steps (Figure 5B,D) [21]. At 100 • DAA (Figure 5A), apart from pericarp tissues, fewer internal tissues are distinguished in the X-ray images probably because their developing cell walls are thinner and because the wheat grains are more highly hydrated (75% and 68% at 100 • DAA and 250 • DAA respectively).…”
Section: High-resolution 3d Imaging Improves Cell Distinction But Gre...mentioning
confidence: 87%
“…Other imaging modalities provide information that would be of interest to relate to the ones obtained from X-ray tomography and microscopy. For example, magnetic resonance imaging gives access to local water status within the grain (e.g., for wheat [21]) but scans are very time-consuming, and spatial resolution is still low (cellular level cannot be reached). Mass-spectrometry imaging reveals chemical composition within tissues with improved discrimination power (e.g., for wheat [41]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, at 28 DAA, the cell walls of the entire endosperm tissue could be distinctly labelled [ 55 ]. Recent research on wheat showed that AX is also found in intracellular vesicles in various grain regions: in the apoplast between the nucellar epidermis and the endosperm tissues, and in the endosperm cavity [ 56 ]. The endosperm cavity separates the nucellar projection from the endosperm transfer cells and it is filled by a viscous, gel-like substance that persists even after desiccation [ 56 , 57 ].…”
Section: The Main Features Of Arabinoxylan In Rye and Wheatmentioning
confidence: 99%